2018
DOI: 10.1080/09593330.2018.1424258
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous extraction and enrichment of reactive dye using green emulsion liquid membrane system

Abstract: Currently, an extractive green palm oil-based emulsion liquid membrane (ELM) has been used for simultaneous extraction and enrichment of Reactive Red 3BS from simulated synthetic dye wastewater. The ELM consists of two main phases, which are organic liquid membrane (LM) and stripping solution. During the extraction process, the ELM was dispersed into the simulated synthetic dye wastewater containing the Reactive Red 3BS complexes. The organic LM contains tridodecylamine (TDA), Sorbitan Monooleate (Span 80) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Noah et al applied ELM for recovery of toxic Cr VI from electroplating wastewater and converted it to less toxic Cr III simultaneously through a sustainable continuous ELM extraction system [50]. Application of green diluents such as vegetable oils in ELM formulation is a new area in ELM development that has been recently applied for extraction and enrichment of reactive dyes [51,52].…”
Section: Introductionmentioning
confidence: 99%
“…Noah et al applied ELM for recovery of toxic Cr VI from electroplating wastewater and converted it to less toxic Cr III simultaneously through a sustainable continuous ELM extraction system [50]. Application of green diluents such as vegetable oils in ELM formulation is a new area in ELM development that has been recently applied for extraction and enrichment of reactive dyes [51,52].…”
Section: Introductionmentioning
confidence: 99%
“…Other advantages of this method are its simple operation, low cost and energy consumption, and efficiency for low concentration of solutes. [ 16,17 ]…”
Section: Introductionmentioning
confidence: 99%
“…According to the authors, both modelling approaches were successful and reasonable results were reported. Othman et al [ 16 ] successfully developed a mathematical model for chromium removal from electroplating wastewater. They used the boundary breakage model considering the emulsion globule approach and the emulsion swelling and breakage during the ELM process, and the derived mass balance for three separated phases, namely, internal, membrane, and feed.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, enrichment processing plays a vital role in the handling of organic wastes in the analytical fields [7,8]. Adsorption is one of the most commonly used approaches for the enrichment of various contaminants including clenbuterol [9], organic dyes [10], inorganic metal ions [11], etc. [7,12], and many kinds of adsorbents have been explored, such as polymer microspheres [13,14], polymer fibers [15], polymer hydrogels [16], waste biomasses [17], activated carbon [18], carbon nanotubes [19], graphene [20], and silica nanoparticles [21].…”
Section: Introductionmentioning
confidence: 99%